Flight simulation of a swashplateless helicopter using rotor RPM variation and movable CG - Krishnamurthi, J.; Gandhi, F. (My University, 2015)
This paper focuses on swashplateless primary control of a helicopter using rotor RPM variation in lieu of rotor collective pitch, and longitudinal and lateral cg motion in lieu of rotor cyclic pitch. Using a model of a swashplateless variant of the UH-60A Black Hawk helicopter, trim results over a range of airspeeds and flight simulation results for the aircraft as it transitions from hover to 70 knots cruise are presented. In the absence of rotor longitudinal cyclic pitch, the rotor tip path plane tilts further back (increasingly negative ?1c) with increasing cruise speed, while the aircraft assumes a heavy nose-down pitch attitude so the rotor can provide a propulsive thrust. Using the horizontal tail slew schedule of the baseline aircraft, a total forward cg travel of 2.48 ft, from the hover position, is required to operate at 120 knots. However, if the horizontal tail slew schedule is modified so that it introduces nose-down pitching moments on the aircraft at higher airspeeds, the required cg travel can be reduced to as little as 0.77 ft for operation from hover to 120 knots cruise. Flight simulation results were carried out in two steps – hover to 40 knots transition flight, and 40 knots to 70 knots cruise corresponding to low power cruise operation, each over a 60 sec interval. The flight simulation results showed that the inertial velocities of the aircraft are well regulated by the controller, and the steady-state values of the controls and rotor flapping at the end of each "maneuver" compare well with the calculated trim values at the speeds achieved.
Keywords: Aircraft Design